Golgi-Related Proteins GOLPH2 (GP73/GOLM1) and GOLPH3 (GOPP1/MIDAS) in Cutaneous Melanoma: Patterns of Expression and Prognostic Significance - Donizy, Piotr (Int J Mol Sci, 2016)
GOLPH2 and GOLPH3 are Golgi-related proteins associated with aggressiveness and progression of a number of cancers. Their prognostic significance in melanoma has not yet been analyzed. We performed immunohistochemical analysis for GOLPH2 and GOLPH3 in 20 normal skin, 30 benign nevi and 100 primary melanoma tissue samples and evaluated their expression in three compartments: cancer cells, tumor-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs). High levels of both proteins in melanoma cells were associated with characteristics of aggressive disease, and shorter disease-free survival (DFS) and cancer-specific overall survival (CSOS). On the contrary, increased numbers of GOLPH2-positive and GOLPH3-positive TAMs were observed in thinner, non-ulcerated tumors, with brisk lymphocytic reaction and absent lymphangioinvasion. Distant metastases were not observed among patients with high numbers of GOLPH2-positive TAMs. Increased expression of either protein in TAMs was related to prolonged CSOS and DFS. Similarly, GOLPH3-expressing CAFs were more frequent in thin melanomas with low mitotic rate, without ulceration and lymphangioinvasion. Moreover, increased GOLPH3-positive CAFs correlated with the absence of regional or distant metastases, and with longer CSOS and DFS. GOLPH2 expression was not observed in CAFs. Our results suggest that GOLPH2 and GOLPH3 play a role in melanoma progression and are potential targets for molecular-based therapies.